Design and Synthesis of Dipeptidomimetic Isocyanonaphthalene as Enhanced-Fluorescent Chemodosimeter for Sensing Mercury Ion and Living Cells - Wang, Xiao-Juan; Li, Gao-Wei; Cheng, Yi-Peng; Sun, Qiu-Ling; Hao, Yuan-Qiang; Wang, Chen-Hong; Liu, Lan-Tao (Frontiers in Chemistry, 2022)
A novel valine-based isocyanonaphthalene (NpI) was designed and synthesized by using an easy method and enabled the selective fluorescence detection of Hg2+. The chemodosimeter can display an immediate turn-on fluorescence response (500-fold) towards target metal ions upon the Hg2+-mediated conversion of isocyano to amino within NpI. Based on this specific reaction, the fluorescence-enhancement probe revealed a high sensitivity toward Hg2+ over other common metal ions and exhibited excellent aqueous solubility, good antijamming capability, high sensitivity (detection limit: 14.2 nM), and real-time detection. The response mechanism of NpI was supported by NMR spectroscopy, MS analysis and DFT theoretical calculation using various techniques. Moreover, a dipeptidomimetic NpI probe was successfully applied to visualize intracellular Hg2+ in living cells and monitor Hg2+ in real water samples with good recoveries and small relative standard deviations.